PENCEGAHAN KECANDUAN GADGET DAN TANTRUM PADA ANAK MELALUI KONSISTENSI POLA ASUH - Ignasia Nila Siwi; Okta Risya Safitri (LPPM STIKES Madani Yogyakarta, 2019)
Gadget addiction and temper are problems that often occur in children now. The results of the preliminary study at the Paud Bunayya Islamic Center in Bin Baz ICBB found that the majority of children of early childhood education have a dependence on gadget and not a few who are temper due to this dependence. Therefore, the right method of prevention of this problems is needed. This community service activity aims to provide education on prevention of gadget addiction and temper in children through the consistency of parenting. The methods used include screening gadget addiction and temper problems, giving education, and evaluating. The results of the activity show inconsistencies in parenting pattern resulting in gadget addiction and temper. Through consistency of parenting, gadget addiction and temper can be prevented and overcome.